2019
DOI: 10.1183/13993003.00732-2019
|View full text |Cite
|
Sign up to set email alerts
|

Whole-transcriptome sequencing reveals heightened inflammation and defective host defence responses in chronic rhinosinusitis with nasal polyps

Abstract: IntroductionThe pathways underlying chronic rhinosinusitis with nasal polyps (CRSwNP) are unclear. We conducted genome-wide gene expression analysis to determine pathways and candidate gene sets associated with CRSwNP.MethodsWe performed whole-transcriptome RNA sequencing on 42 polyp (CRSwNP-NP) and 33 paired nonpolyp inferior turbinate (CRSwNP-IT) tissues from patients with CRSwNP and 28 inferior turbinate samples from non-CRS controls (CS-IT). We analysed the differentially expressed genes (DEGs) and the gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 37 publications
12
42
0
Order By: Relevance
“…Our ndings for RNA sequencing provides valuable information for exploring the general molecular mechanisms underlying the pathogenesis of CRSwNP. Similar to the ndings of Peng and colleagues [40], our study has demonstrated that regardless of the subtypes of CRSwNP, genes and pathways that most likely contribute to the pathogenesis of CRSwNP, appear to be mainly associated with cytokine and chemokine signalling pathway, staphylococcus aureus infection, eicosanoid metabolism and cell adhesion molecules. In this respect, the well-known genes or biomarkers closely related to CRSwNP; for example CLC, POSTN, CCL18, IL13, TSLP and BPIFA1; were also identi ed as the top DE-mRNAs in both CRSwNP-alone and CRSwNP+AS groups.…”
Section: Discussionsupporting
confidence: 88%
“…Our ndings for RNA sequencing provides valuable information for exploring the general molecular mechanisms underlying the pathogenesis of CRSwNP. Similar to the ndings of Peng and colleagues [40], our study has demonstrated that regardless of the subtypes of CRSwNP, genes and pathways that most likely contribute to the pathogenesis of CRSwNP, appear to be mainly associated with cytokine and chemokine signalling pathway, staphylococcus aureus infection, eicosanoid metabolism and cell adhesion molecules. In this respect, the well-known genes or biomarkers closely related to CRSwNP; for example CLC, POSTN, CCL18, IL13, TSLP and BPIFA1; were also identi ed as the top DE-mRNAs in both CRSwNP-alone and CRSwNP+AS groups.…”
Section: Discussionsupporting
confidence: 88%
“…Our findings for RNA sequencing provides valuable information for exploring the general molecular mechanisms underlying the pathogenesis of CRSwNP. Similar to the findings of Peng and colleagues [40], our study has demonstrated that regardless of the subtypes of CRSwNP, genes and pathways that most likely contribute to the pathogenesis of CRSwNP, appear to be mainly associated with cytokine and chemokine signalling pathway, and yellow module (f) visualized by cytoscape network. mRNAs or lncRNAs with high connectivity and edges with weight above a threshold of 0.1 were identified as hub genes.…”
Section: Discussionsupporting
confidence: 88%
“…Our RNA sequencing data provides valuable information for exploring the general molecular mechanisms underlying the pathogenesis of CRSwNP. Regardless of the subtypes of CRSwNP, genes and pathways that most likely contribute to the pathogenesis of CRSwNP might be mainly associated with cytokine and chemokine signaling pathway, staphylococcus aureus infection, eicosanoid metabolism and cell adhesion molecules, which were similar to Peng's findings [28]. The well-known genes or biomarkers closely related to CRSwNP such as CLC, POSTN, CCL18, IL13, TSLP and BPIFA1…”
Section: Discussionsupporting
confidence: 71%